Effect of Investment Decisions and Debt Policy in Company Value - Ade Aisah Putri Insani Chaniago; Muhammad Irsan (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This study aims to analyze the influence of investment decisions and debt policies on firm value in LQ45 issuers listed on the Indonesia Stock Exchange for the 2022–2024 period. Investment decisions are calculated using the Price Earnings Ratio (PER), debt policy is calculated using the Debt to Equity Ratio (DER), and firm value is calculated using Price to Book Value (PBV). The research method used is causal associative with a quantitative approach and utilizes secondary data. The population in this study consists of 63 LQ45 companies listed on the Indonesia Stock Exchange during 2022–2024. The sample was determined using a purposive sampling technique, resulting in 18 companies with 54 observation data. However, there were 13 outliers, resulting in a final sample of 41 observation data. The results show that both partially and simultaneously, investment decisions (PER) and debt policies (DER) have a positive and significant influence on firm value (PBV).